2022
DOI: 10.3389/fimmu.2022.1026070
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in circulating markers in HIV/AIDS patients with poor immune reconstitution: Novel insights from microbial translocation and innate immunity

Abstract: After long-term anti-retroviral therapy (ART) treatment, most human immunodeficiency virus (HIV)/Acquired Immure Deficiency Syndrome (AIDS) patients can achieve virological suppression and gradual recovery of CD4+ T-lymphocyte (CD4+ T cell) counts. However, some patients still fail to attain normal CD4+ T cell counts; this group of patients are called immune non-responders (INRs), and these patients show severe immune dysfunction. The potential mechanism of poor immune reconstitution (PIR) remains unclear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 145 publications
1
4
0
Order By: Relevance
“…Among all participants, the number of INRs was 826, accounting for 21.8%, including 21.8% and 22.0% in the training and validation sets, respectively. These outcomes corroborated a previous study that found a percentage of INRs in PLWH of 15–30% [ 31 ]. For early diagnosis and treatment, in this study, we developed and validated a feasible and simple visual nomogram as a new approach for predicting the development of immune recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Among all participants, the number of INRs was 826, accounting for 21.8%, including 21.8% and 22.0% in the training and validation sets, respectively. These outcomes corroborated a previous study that found a percentage of INRs in PLWH of 15–30% [ 31 ]. For early diagnosis and treatment, in this study, we developed and validated a feasible and simple visual nomogram as a new approach for predicting the development of immune recovery.…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of INR in HIV/AIDS patients may be affected by multiple factors, mainly including decreased bone marrow hematopoiesis, insufficient thymus output, residual virus replication, co-infection during ART, intestinal flora translocation, abnormal immune activation, type of antiretroviral regimen, baseline CD4 + T cell levels, age, sex, and genetic characteristics ( 4 , 9 ). However, the precise mechanisms underlying INR remain an extremely challenging issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the complete suppression of HIV replication with ART, 15-30% of patients fail to recover their CD4 + T-cell counts and do not achieve optimal recovery. [1][2][3] These individuals are referred to as immunological non-responders (INRs). [4] After 4-7 years of combined ART (cART), patients with CD4 + T-cell counts below 350-500 cells/mL are classified as INRs, while those with counts above 500 cells/mL are defined as immunological responders (IRs).…”
Section: Introductionmentioning
confidence: 99%